CHItaly 2021: 14th Biannual Conference of the Italian SIGCHI Chapter 2021
DOI: 10.1145/3464385.3464731
|View full text |Cite
|
Sign up to set email alerts
|

Expressive digital place making as means of aggregation.

Abstract: Where are the frontiers of Human-Computer Interaction? What theories, methodologies, tools, and sensitivities do researchers, designers and practitioners need to explore uncharted territories? These are the questions that inspired CHItaly 2021, the 14th edition of the biannual conference of the Italian SIGCHI Chapter. Some initial answers are documented in the proceedings and summarised in this foreword alongside a reflection on future frontiers of hybrid scientific conferences.The original focus of inquiry wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…Furthermore, some authors mention these terms in their work without defining them (Alvarez et al, 2017;Besek, 2021; Table 2 Study selection chart. Bicquelet-Lock, 2021;Breek et al, 2018Breek et al, , 2021Busse, 2021;Chaudhry et al, 2019;Cilliers et al, 2015;Clowater, 2021;Edwards et al, 2020;Globa et al, 2019;Gobbo and Benedetti, 2021;Harner et al, 2017;Houghton et al, 2015;Hunter et al, 2022;MacIntyre et al, 2019;Marshall, 2021;Mcarthur and Xu, 2021;Ozduzen et al, 2021;Rzeszewski and Naji, 2022;Soedarsono et al, 2021;Truong et al, 2022;Wright, 2021;Zhang and Gong, 2021). The absence of an explicit clarification of these concepts presented from the results of the analysis, as well as the different terms employed, emphasizes the confusion and lack of consensus on digital placemaking.…”
Section: Theoretical Perspectives On Digital Placemakingmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, some authors mention these terms in their work without defining them (Alvarez et al, 2017;Besek, 2021; Table 2 Study selection chart. Bicquelet-Lock, 2021;Breek et al, 2018Breek et al, , 2021Busse, 2021;Chaudhry et al, 2019;Cilliers et al, 2015;Clowater, 2021;Edwards et al, 2020;Globa et al, 2019;Gobbo and Benedetti, 2021;Harner et al, 2017;Houghton et al, 2015;Hunter et al, 2022;MacIntyre et al, 2019;Marshall, 2021;Mcarthur and Xu, 2021;Ozduzen et al, 2021;Rzeszewski and Naji, 2022;Soedarsono et al, 2021;Truong et al, 2022;Wright, 2021;Zhang and Gong, 2021). The absence of an explicit clarification of these concepts presented from the results of the analysis, as well as the different terms employed, emphasizes the confusion and lack of consensus on digital placemaking.…”
Section: Theoretical Perspectives On Digital Placemakingmentioning
confidence: 99%
“…Location-based technology is found as an essential element of hybrid realities, which is also understood as a key characteristic of digital placemaking (Clarke, 2021;Keegan, 2021;MacIntyre et al 2019;Witteborn, 2021). Results of the review showed that hybrid realities include location-based technology and games (Bilandzic and Johnson, 2013;Frith and Richter, 2021;Gobbo and Benedetti, 2021;Harner et al, 2017;Hjorth and Richardson, 2017;Pavlovskaya, 2016;Qabshoqa, 2018), augmented realities (Abdel-Aziz et al, 2016;Boffi, 2021;Clowater, 2021;Her, 2021;Hjorth and Richardson, 2017;Hunter et al, 2022;, immersive digital experiences (Globa et al, 2019), virtual reality (Kuchelmeister et al, 2020;Rzeszewski and Naji, 2022;van Houwelingen-Snippe et al, 2021), and digital pop-up artefacts (Fredericks et al, 2018). All of them help create realities that combine the physical and digital world with different intensitiesvirtual reality refers to a fully immersive experience in the digital environment, in contrast to digital pop-up artefacts that combine analogue and digital media for community engagement.…”
Section: Key Characteristicsmentioning
confidence: 99%